House While Woman Grows - Şengül Öymen Gür; Şengül Yalçınkaya Erol (Iconarp International Journal of Architecture and Planning, 2013)
Discourses on woman/space relations boomed in the 90s. The fundamental reason was to give support to the Feminist Movement. This trend which has had feeble effect on architectural design remained controversial. The comprehensive research expounded in this article which was based on an open-ended questionnaire that targeted at determining the gender roles at home, applied to female subjects who simulated the national demographics, clearly demonstrated that the home experience of an average Turkish woman basically consists of kitchens; the female who runs the house does not really have a place for herself at home. However she does not perceive her restrained, secondary role an issue worthy of struggling to change and she grants spaces for recreation and study to the male. The well-established civil laws conducive for equality has not changed this disturbing situation and do not seem to do so in the near future.